GAMBARAN PENERAPAN PROTOKOL KESEHATAN PADA REMAJA SEKAA TRUNA TRUNI BATUR SELATAN DI MASA PANDEMI - Gita, Ayu Indah; Sawitri, Ni Komang Ari; Sri Krisnawati, Komang Menik (Coping: Community of Publishing in Nursing; Vol 9 No 5 (2021): Oktober 2021, 2021)
Coronavirus Disease 2019 or Covid-19 is a disease that attacks the respiratory system that can spread very fast. The implementation of the health protocol is an effort made by the government to break the chain of spreading Covid-19. The purpose of this study was to describe the implementation of health protocols in adolescents of STT Batur Selatan during the pandemic time. This research is a descriptive quantitative study with a cross sectional approach. The number of respondents in this study was 105 adolescents who were selected by purposive sampling technique. The research data collection was held for one month starting from March-April 2021. The research instrument used was a research instrument compiled by the researcher based on literature review and the Guidelines for the Prevention and Control of Coronavirus Disease (Covid-19) from The Ministry of Health of the Republic of Indonesia. The results of this study indicate that the majority of respondents are male (50.5%), in the age range of 20-22 (55.2%), have high school / vocational education (70.5%), unemployed (71.4%), live in the hometown (62.9%), and often back to hometown (53.8%). The implementation of health protocols in adolescents of STT Batur Selatan was mostly in the poor implementation category (51.4%), while the rest (48.6%) were in the good implementation category.